Louise Moillon - Stevenson, Lesley (Getty Publications, 2024)
The life and career of Louise Moillon (1609/10-1696) offers a fascinating case study of a supremely talented artist whose posthumous reputation has been mired in invisibility. Born and raised in Paris, Moillon was the sole woman in a circle of Calvinist Protestant émigrés who brought their tradition of still-life painting with them from Flanders. During her lifetime, she was able to enjoy a degree of professional independence and attract enough recognition to be regarded as on a level with her male counterparts, yet her exquisite work and enigmatic story are little known today. This illustrated biography examines some of the ways in which Moillon's story has been represented since the revival of interest in her work and draws on recent scholarship to situate the painter in her rightful place. Offering a sweeping exploration of the genre of still life, this book also chronicles how a woman in early modern France was able to capture the attention of the artistic world while dissecting why her prominence waned in the centuries following her death
Keywords: Moillon, Louise -- 1610-1696; Moillon, Louise / 1610-1696; Women painters / France / Biography; Painters / France / Biography; Still-life painting, French / 17th century; Femmes peintres / France / Biographies; Peintres / France / Biographies; Nature morte française / 17e siècle; Biografie